"All generations shall call me blessed": A Baptist recovery of Mary1. (May 2017) - Newman, Elizabeth
In Baptist life, Mary typically appears only at Christmas. Accordingly, there is minimal theological reflection on Mary as a resource for ecclesial self-understanding. This article argues for embracing Mary as a figure of the church. Rightly understood, a richer Scriptural reading of Mary can both enhance Baptist (and more broadly Protestant) ecclesiology as well as contribute to the unity of the church.